Curing of an epoxy adhesive with fixed‐frequency microwaves in the presence of a microwave absorber (activated carbon) and with the variable frequency microwave method. Issue 45 (18th August 2022) - Horikoshi, Satoshi; Arai, Yuhei; Mura, Haruka; Serpone, Nick
Abstract: This study examines the curing characteristics of an epoxy resin adhesive mixed with activated carbon (AC) particulates as the microwave absorption heating element (MAHE) using a non‐fluctuating microwave irradiation device consisting of a semiconductor microwave generator and a single‐mode applicator. The advantages of the microwave curing method are the more rapid heating of the epoxy resin adhesive and the associated reduction in curing time. However, problems arose unique to microwave heating as the AC particulates formed aggregates as a result of the microwaves' electric field ( E ‐field), which also led to a temperature distribution greater than 100°C generated in the epoxy resin adhesive. This problem could not be resolved by commercial microwave chemical equipment. Resolution of the problem was achieved using a variable frequency microwave (VFM) irradiation method using a semiconductor generator; high‐speed electrical diffusion of the E ‐field was performed to irradiate with an average electric field without fluctuations. This achieved a uniform curing of the adhesive containing the MAHE particulates using the VFM method, which also proved effective in preventing adhesive ignition accidents. E ‐field was performed to irradiate with an average electric field without fluctuations. This achieved a uniform curing of the adhesive containing the MAHE particulates using the VFM method, which also proved effective in preventing adhesive ignition accidents. Abstract : High‐quality microwave curing of epoxy adhesive containing activated carbon (AC) particulates as microwave absorption heating elements (MAHE) by the variable frequency microwave (VFM) method, and low‐quality microwave curing of epoxy adhesive containing AC particles by the fixed frequency microwave (FFM) method.